INDONESIAN DEMOCRACY AND POLITICAL PARTIES AFTER TWENTY YEARS OF REFORMATION: A CONTEXTUAL ANALYSIS - Ulum, Muhammad Bahrul (Indonesia Law Review, 2020)
This paper traces the trajectory of Indonesian democracy that has developed in the last twenty years, specifically regarding the extent to which its continuities and changes have been consistent with the rationale for reformation. It enquires whether the current democracy has been transformed based on liberal constitutionalism or the new democracy has restored the integralist ideal. In recent years, the mass protests that increasingly color Indonesian politics have become a critical response to a failing system. This analysis asserts that the lack of functioning political parties in Indonesia and the breakdown of Indonesian democracy as a result of integralism ignores essential checks and balances. The situation is exemplified by the cooperation of the opposition parties in the cabinet, including the promotion of gotong royong (mutual help) in the form of Prabowo Subianto, Joko Widodo’s rival in the 2019 Presidential Election. Subianto has long been implicated in human rights abuses, going back to East Timor invasion in the 1970s. This attitude also indicates the serious threat that gradually negates the hard-won liberal democracy at the dawn of the reformation. Among these trends, the current democracy reveals the ineptness of the existing political parties that were essentially liberalized in the early Reformation. As it stands, they have been unable to prevent the current system from being led to a more autocratic model.